2009
DOI: 10.1038/sj.bjc.6605321
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bowel cancer registration data in England, 1996–2004

Abstract: BACKGROUND: The National Health Service (NHS) bowel cancer screening programme (BCSP) was initiated across England in April 2006. To determine the feasibility of using national cancer registration data to assess the impact of the BCSP on stage-specific incidence, we studied trends in the incidence rates of colon (ICD10 C18) and rectosigmoid junction and rectum (ICD10 C19 -C20) cancers and the completeness of data on Dukes stage in England. METHODS: Data were obtained from all nine cancer registries for the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
4
2
0
Order By: Relevance
“…The increases in survival of CRC patients seen across all regions of Europe are consistent with observations of recent major declines in mortality rates,3, 4 along with persistent increase, leveling off or recent slight decrease in incidence rates reported from European countries 15–18. Increases in incidence rates are ongoing in Eastern European countries and have been associated with increases in risk factors associated with “Westernization,” such as obesity and physical inactivity 2.…”
Section: Discussionsupporting
confidence: 81%
“…The increases in survival of CRC patients seen across all regions of Europe are consistent with observations of recent major declines in mortality rates,3, 4 along with persistent increase, leveling off or recent slight decrease in incidence rates reported from European countries 15–18. Increases in incidence rates are ongoing in Eastern European countries and have been associated with increases in risk factors associated with “Westernization,” such as obesity and physical inactivity 2.…”
Section: Discussionsupporting
confidence: 81%
“…When compared with reports from developed countries (Moore et al, 2010) (Sankaranarayanan et al, 2010), the mean age at diagnosis of CRC is lower in the Kingdom. In England, some researchers reported that between 1996 and 2004 the mean age at diagnosis of CRC was 68.4 years in men and 69.0 years in women (Jones et al, 2009); In Australia, the median age at diagnosis of CRC in 2008 was reported to be 70 years (Ageing, 2008), similar to that is reported in the United States (Liang, 2010) and Sweden (Derwinger et al, 2010). Contrary to our findings, reports from neighboring countries that share our country's topographic and climatic characteristics show that patients younger than 45 years of age have more advanced disease at the time of diagnosis when compared with those older than 45 (Al-Jaberi et al, 2003).…”
Section: Discussionsupporting
confidence: 61%
“…The unstaged category included: non-resected patients with no clinical evidence of metastases at diagnosis, resected patients but for whom the registry did not capture the stage, and patients who received potentially downstaging radiotherapy or chemoradiotherapy before surgery. Localised cancers were defined by Duke's A & B and advanced cancers were defined by Duke's C &D. Stage at diagnosis was unknown for almost 18% and 7% of English and French patients, respectively (these percentages are comparable to previous studies) (Jones et al , 2009). …”
Section: Methodssupporting
confidence: 65%